Household Livelihood Strategies Following the Decline of Shrimp Pond Productivity in Bumi Dipasena, Tulang Bawang, Indonesia - Kurniawan, Ilham Hadi; Rochana, Erna (Jurnal Dinamika Sosial Ekonomi, 2025)
Bumi Dipasena in Tulang Bawang Regency, Lampung Province, was once the largest shrimp farming area in Southeast Asia and played a major role in Indonesia’s shrimp exports. Since the early 2000s, shrimp pond productivity has declined due to institutional conflicts, infrastructure degradation, limited access to capital, and unstable production systems, resulting in reduced household income and economic pressure on local communities. This study aims to identify and analyze household livelihood strategies following the decline of shrimp pond productivity in Bumi Dipasena. The research employs a qualitative descriptive approach based on secondary data, utilizing official statistics, government reports, scientific publications, and credible media sources. Data were analyzed through descriptive qualitative analysis, including data reduction, thematic categorization, and identification of livelihood strategy patterns. The findings show that households respond to the decline by diversifying income into informal sectors, small-scale trade, labor migration, and increased reliance on social networks. These livelihood strategies reflect household-level economic responses to prolonged structural changes after the collapse of shrimp farming as the primary livelihood source. This study contributes to socio-economic and development studies by providing empirical insights into household livelihood reorganization in post-aquaculture decline contexts and offers policy-relevant input for sustainable livelihood support in coastal areas.